Deformation-induced charge redistribution in ceria thin film at room temperature - Park, Kyoung-Won; Kim, Chang Sub (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Tuning electronic properties through strain engineering of metal oxides is an important step toward understanding electrochemical and catalytic reactions in energy storage and conversion devices. Traditionally, strain engineering studies focused on movement of oxygen ions at high temperatures (500 degrees C and above), complicating electrical properties by introducing mixed electronic and ionic conductivity. In this study, we demonstrate formation of oxygen vacancies and room temperature charge redistribution in a CeO2 thin film as a result of phase transformation in a localized region by mechanical deformation. Mechanical indentation of the CeO2 thin film at room temperature results in irreversible deformation. Conductive-tip atomic force microscopy (C-AFM) analysis shows increased current passing through the locally deformed area of the CeO2 thin film. Electron energy loss spectroscopy (EELS) analysis equipped with transmission electron microscopy (TEM) suggests that the increase in current contrast in the deformed region arises from an increased concentration of Ce3+ ions. We herein discuss the fundamental reason behind the increased amount of Ce3+ ions in the deformed area, based on the atomic scale computational works performed by molecular dynamics (MD) simulations and first-principles density functional theory (DFT) calculations, and scanning transmission electron microscopy (STEM) analyses. Mechanical deformation not only facilitates the formation of oxygen vacancies in a localized region, but also induces a phase transformation of cubic fluorite CeO2 into a newly formed T-CeO2 structure. These are considered as the critical factors for the enhanced current in the deformed CeO2 thin film at room temperature. (C) 2020 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: INITIO MOLECULAR-DYNAMICS; SPACE-CHARGE; GRAIN-BOUNDARY; ELECTRICAL-PROPERTIES; IONIC-CONDUCTIVITY; OXYGEN; CEO2; SEMICONDUCTOR; STATE; POLARIZATION